Comprehensive Analysis of Titanium Oxide Nanoparticle Size and Surface Properties on Neuronal PC-12 Cells: Unraveling Cytotoxicity, Dopaminergic Gene Expression, and Acetylcholinesterase Inhibition - Jitendra Kumar Suthar; Balaji Rakesh; Anuradha Vaidya; Selvan Ravindran (Journal of Xenobiotics, 2023)
Titanium oxide nanoparticles can penetrate the blood–brain barrier, infiltrate the central nervous system, and induce neurotoxicity. One of the most often utilized nanoparticles has been investigated for their neurotoxicity in many studies. Nonetheless, there remains an unexplored aspect regarding the comparative analysis of particles varying in size and nanoparticles of identical dimensions, both with and devoid of surface coating. In the current study, we synthesized two differently sized nanoparticles, TiO2-10 (10 nm) and TiO2-22 (22 nm), and nanoparticles of the same size but with a polyvinylpyrrolidone surface coating (TiO2-PVP, 22 nm) and studied their toxic effects on neural PC-12 cells. The results highlighted significant dose- and time-dependent cytotoxicity at concentrations ≥10 μg/mL. The exposure of TiO2 nanoparticles significantly elevated reactive oxygen and nitrogen species levels, IL-6 and TNF-α levels, altered the mitochondrial membrane potential, and enhanced apoptosis-related caspase-3 activity, irrespective of size and surface coating. The interaction of the nanoparticles with acetylcholinesterase enzyme activity was also investigated, and the results revealed a dose-dependent suppression of enzymatic activity. However, the gene expression studies indicated no effect on the expression of all six genes associated with the dopaminergic system upon exposure to 10 μg/mL for any nanoparticle. The results demonstrated no significant difference between the outcomes of TiO2-10 and TiO2-22 NPs. However, the polyvinylpyrrolidone surface coating was able to attenuate the neurotoxic effects. These findings suggest that as the TiO2 nanoparticles get smaller (towards 0 nm), they might promote apoptosis and inflammatory reactions in neural cells via oxidative stress, irrespective of their size.